Dampak Pertumbuhan Sektoral terhadap Ketimpangan Pendapatan dan Kemiskinan di Indonesia: Analisis menggunakan Social Accounting Matrix dan Micro-Simulation - Winarni, Diny Tri; Hartono, Djoni (UI Scholars Hub, 2023)
Based on extended Indonesia’s Social Accounting Matrix (SAM) 2015 and using the micro-simulation method, this study shows how sectoral growth affects income inequality and poverty in Indonesia and the contribution of the Small and Medium Enterprises (SMEs) manufacturing sector in reducing income inequality. Of the 24 sectors in Indonesia, only the growth in 10 sectors can reduce income inequality, with the largest reduction being growth in other agricultural crop sector. On the other hand, SMEs have no notable effect on reducing income inequality. Although the impact depends on which sector the SME is in. This study also shows that growth in all economic sectors has an impact on poverty alleviation in different contributions. Growth in other agriculture crop sector contributed the largest to poverty alleviation in Indonesia.